Development of a health coaching model to improve caregivers’ ability to care for patients with mental disorders - Andriani, Andriani; Yusuf, Ah; Fitryasari, Rizki; Kadar, Kusrini S.; Basrah, Miftahul Jannah; Sarih, Karmila; Fitriani, Nurlaila; Arsyad, Dian Sidik; Setialaksana, Wirawan (Jurnal Ners, 2025)
Introduction: This study aimed to develop a health coaching model grounded in these theoretical frameworks. Methods: An explanatory cross-sectional design was employed, involving 155 caregivers purposively recruited from seven primary health care centers in Makassar, Indonesia. Eligible participants were primary caregivers from nuclear or extended families, aged ≥18, with complete contact information, available for home visits, and referred by the mental health program coordinator. Study variables included family, caregiver, patient, nurse, and health care service factors, as well as health coaching, planned behavior, behavioral intention, and caregiver ability. Data were collected between February to June 2024 using structured questionnaires and analyzed with Partial Least Squares-Structural Equation Modeling (SmartPLS v3.8). Results: The family, patient, and nurse-related factors significantly affected health coaching. These factors, along with caregiver characteristics, also affected planned behavior, which in turn significantly influenced behavioral intention and caregiver ability. Conclusions: Health coaching directly improved caregivers’ capability. These findings highlight the importance of comprehensive health coaching and family-centered training as integral components of mental health services.